Hamid Algar, Religion and State in Iran, 1785-1906; The Ulema in the Qajar Period, University of California Press, Berkeley, California, 1969. Mirza Malkum Khan; a Biographical Study in Iranian Modernism, University of California Press, Berkeley, California, 1973. - W., M. (Estudios de Asia y África, 1974)
-